Preservation of Boer Cross Buck Spermatozoa Motility and Viability in Tris Albumin Extender Supplemented with Fig Fruit Filtrates in Cold Temperature Storage: - - Triyani, Rika Subarniati; Zaenuri, Lalu Ahmad; Sumadiasa, I Wayan Lanus; Lukman HY (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Semen quality is one of the most important factors for the success of artificial insemination. The quality of the diluent really determines the quality of the liquid semen. Therefore, research to find the most optimal diluent to maintain the quality of liquid semen, whether stored at room temperature, cold or frozen, is continuously being carried out. The aim of this research was to determine the motility and viability of Boer cross goat spermatozoa in Tris albumin extender supplemented with fig fruit filtrate and stored at cold temperatures. This study used a completely randomized design (CRD) with 4 treatments, namely P0 (standard Tris extender + 2.5% egg yolk), Pl (Tris standard extender + 2.5% albumin), P2 (P1 + 4% fig fruit filtrate), and P3 (P1+6% fig fruit filtrate). Evaluation of fresh semen includes volume, color, aroma, consistency, degree of acidity (pH), mass motility, individual motility and spermatozoa viability. The variables observed in this study were individual motility and spermatozoa viability up to a minimum motility limit of 40%. The results showed that the addition of fig filtrate to the Tris-albumin based extender did not increase the ability of the extender to maintain spermatozoa motility and viability compared to the standard Tris-egg yolk extender. In conclusion, the addition of fig fruit filtrate to the Tris egg albumin extender had no better effect than the standard Tris-egg yolk extender. To get better results, further studies are needed on various concentration combinations between albumin and fig fruit filtrate in Tris-albumin based.